IMPROVING STUDENTS VOCABULARY IN DESCRIPTIVE TEXT THROUGH WORD WALL - Hanny, Ester; Rosnija, Eni; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was done to know how the use of word wall as the media can improve students’ vocabulary on descriptive text especially on adjective words. This research is designed as a classroom action research on the second grade students of SMP LKIA Pontianak in academic year 2017/2018. The researcher used observation checklist, field notes, and test to collect data. The data were analyzed qualitatively and quantitatively. The result showed that the students’ vocabulary in each cycles has improved during their discussion and performance in applying each steps of word wall. The students discussed in a group in selecting the words, pictures were also functioned to help them finding the meaning of the words. The students interacted with each other to finish their work sheet. They gave and asked for opinions to each other in the process of selecting the words. The teacher also took a role in that process. Although, some students did not speak up, they still paid attention to their groups. When they performed their word wall, each student had their roles. The improvement of students’ vocabulary is also shown by mean score of the students’ tests. In the first cycle, the students’ mean score was 50.45 it increased to 76.02 in the second cycle. In conclusion, the findings confirmed that the use of word wall as a media can improve students’ vocabulary on descriptive text. Key words: Descriptive text, Vocabulary, Word wall